2020
DOI: 10.1038/s41598-020-66250-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cebranopadol on Cocaine-induced Hyperactivity and Cocaine Pharmacokinetics in Rats

Abstract: Cebranopadol is known as a highly potent analgesic. Recent studies also demonstrated that administration of cebranopadol significantly decreased cocaine self-administration and significantly reduced cue-induced cocaine-seeking behaviors in rats. However, it was unclear whether these interesting behavioral observations are related to any potential effects of cebranopadol on cocaine pharmacokinetics or cocaine-induced hyperactivity. In principle, a promising therapeutic candidate for cocaine dependence treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…In these experiments, no significant effects of cebranopadol on cocaine kinetics were detected [40]. However, despite the fact that cebranopadol decreases cocaine self-intake, Wei et al indicated that cebranopadol at the dose of 50 ug/kg potentiated cocaine-induced hyperactivity [40]. According to Shen et al, the mechanism of action of cebranopadol on cocaine self-administration is based on two possibly independent mechanisms involving NOP and the classical opioid receptor, as only the simultaneous blockade of both these pathways determines the inhibition of cocaine self-intake [39].…”
Section: Cebranopadol-abuse Potential and Drug Dependencementioning
confidence: 59%
See 1 more Smart Citation
“…In these experiments, no significant effects of cebranopadol on cocaine kinetics were detected [40]. However, despite the fact that cebranopadol decreases cocaine self-intake, Wei et al indicated that cebranopadol at the dose of 50 ug/kg potentiated cocaine-induced hyperactivity [40]. According to Shen et al, the mechanism of action of cebranopadol on cocaine self-administration is based on two possibly independent mechanisms involving NOP and the classical opioid receptor, as only the simultaneous blockade of both these pathways determines the inhibition of cocaine self-intake [39].…”
Section: Cebranopadol-abuse Potential and Drug Dependencementioning
confidence: 59%
“…Subsequently, Wei et al examined the influence of cebranopadol on cocaine kinetics. In these experiments, no significant effects of cebranopadol on cocaine kinetics were detected [40]. However, despite the fact that cebranopadol decreases cocaine self-intake, Wei et al indicated that cebranopadol at the dose of 50 ug/kg potentiated cocaine-induced hyperactivity [40].…”
Section: Cebranopadol-abuse Potential and Drug Dependencementioning
confidence: 87%
“…Interestingly, clinically used buprenorphine which shows partial agonism at both MOP and NOP, has a phosphorylation profile similar to AT-201 wherein it stimulates only S375 phosphorylation at MOP but none at NOP 20 , 21 Cebranopadol showed a more ‘MOP-dominant’ profile and partial to high efficacy at NOP in G protein signaling assays. Despite its clinical efficacy in pain, cebranopadol has been reported to produce reinforcing effects in rats, nonhuman primates and produced drug liking in human clinical trials 48 , 58 , 59 . Correspondingly, it elicited strong multi-site phosphorylation at MOP and weak NOP phosphorylation at S346.…”
Section: Discussionmentioning
confidence: 99%
“…The NCGIG rats and GUGIG rats were weighed and given a single dose of 20 mg/kg, 40 mg/kg, or 60 mg/kg troxipide (10 mL/kg) via intragastric administration. The rat blood collection method used in our study was performed according to ICH guidelines and the guidelines of the Nonclinical Pharmacokinetics of Medicinal Products by National Medical Products Administration (NMPA) and was based on previous reports and our preliminary studies 90 92 . The approximately 0.3 mL of plasma was collected from the orbital venous plexus of the NCGIG and GUGIG rats before administration and 15, 30, 60, 120, 180, 240, 360, 480, 600, 720, 1,440, 2,160, 2,880 min after administration .…”
Section: Methodsmentioning
confidence: 99%